Ethnopharmacological Study of Medicinal Plants in the Rawamerta Region Karawang, West Java, Indonesia - Nuraeni, Eni; Alkandahri, Maulana Yusuf; Tanuwidjaja, Sri Mulyanthy; Fadhilah, Khuzaimah Nurul; Kurnia, Gita Silpiani; Indah, Dedeh; Permana, Adam; Hasanah, Arum; Ahmad, Farid; Barkah, Dikdik Caesar; Ningsih, Siti Ningrum Ratna; Khoerunnisa, Asyri; et al. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Traditional medicinal plants’ application has significant advantages for cultural development, acceptability, and economic affordability. Furthermore, they are claimed to cure several types of diseases compared to modern medicines. AIM: This study aims to document and preserve the use of ethnomedicinal plants to treat various diseases by the community in the Rawamerta Region, Karawang, West Java, Indonesia. METHODS: Fieldwork was carried out from January to August 2022 through face-to-face interviews, questionnaires, and discussions. Plant species were identified based on standard taxonomic methods, floral morphological characteristics, and possibly, by using samples for comparison, as well as expert consultation and literature. They were then grouped into families according to the Cronquist classification system. Furthermore, their names were checked on the Plant List (www.plantlist.org) and the International Plant Name Index (www.ipni.org). RESULTS: It was discovered that 50 plant species belonging to 31 families spread across 46 genera are employed for the treatment of various diseases in Rawamerta, such as diabetes, inflammation, hypertension, fever, dyslipidemia, antiseptic, gastric disorders, anticancer, cough, gout, etc. Based on the results, Acanthaceae, Fabaceae, Zingiberaceae, and Myrtaceae are the most dominant families applied for the treatment purpose. Meanwhile, the most frequently used genera are Syzygium, Piper, Curcuma, and Annona. The plant part majorly used in medicine preparation is the leaf (64%), followed by fruit (14%), rhizome (10%), and stem (6%), as well as flower, peel, and stem and leaf (2%, respectively). The most commonly applied preparation method is an infusion (48%), followed by decoction (44%), juice (4%), as well as paste and drops (2%, respectively). This study also showed more than one plant species is used for treating the same disease. CONCLUSION: The results confirm that the Sundanese people in Rawamerta still rely heavily on medicinal plants for their health-care system. However, efforts to preserve medicinal plants and local wisdom in the region have not been significant. Therefore, the indigenes and the government are advised to carry out in situ and ex situ conservation strategies to maintain the availability of medicinal plants in the region.